Modification of the Altman Model Z Score: Indicator of Financial stability (Docentes 2.0 Journal, 2022)
A primary strategy is to place funds in a solid financial institution, totally free of any economic stress, financial problems, or suspicions of instability over time. This research was developed to apply a modification to the Altman Z-Score model as an indicator of economic stability for the Banco de Finanzas de Nicaragua case in 2022. It is developed under the analytic-synthetic method, pragmatic paradigm, hybrid approach, hypothetical-deductive type, and contemporary triangular design. Interviews with experts and officials support the qualitative factor. The quantitative is represented in a sample of historical financial statements 2016 -2021, published by the Superintendency of Banks and Other Financial Institutions - SIBOIF. The multiple linear regression model was obtained as a statistical tool through the IBM SPSS Statistics 23.0 program. New coefficients and response ranges will modify the Altman Model for use in the Banco de Finanzas. The modification of the Altman ???? Score Model will substantially contribute to Banco de Finanzas' business management, supporting its analysis and financial estimates for efficient decision making; predicting future stability behaviors for the year 2022. Finally, its application by the SIBOIF can be recommended, representing an approximation, test, or test to be considered as a prudential regulation.
Keywords: Modification; indicator; financial stability; companies